Globalization as the Constraint Factor of the European Union-United States TTIP - Alunaza SD, Hardi; Sherin, Virginia (Global Local Interactions: Journal of International Relations, 2019)
This paper aims to explain the impact of globalization on Transatlantic Trade and Investment Partnership (TTIP) agreement between European Union (EU) and United States (US). Regarding its implementation, TTIP received negative response. The main policies in TTIP agreement will burden the access of Europeans' businesses to compete on local and national scale. Through the free market, Made in America products will enter the European market, which will certainly cause a decline in demand for Europeans’ local products. As a result, the Europeans believed that benefits of TTIP only be felt by a few people. This paper attempts to explain the problem using the theory of foreign policy and the theory of globalization. The author uses qualitative research methods with data collection techniques through literature studies. The results of this paper show that Europeans considered TTIP agreement as a form of hegemony from private corporations to the governments of EU countries as an impact of globalization process. This criticism has finally become a challenge for EU national authorities to implementing the TTIP so that this agreement postponed in October 2016 and still has not continued until now.